Implementation of the Stunting Supplemental Feeding Program in Samataring Village, Sinjai Regency - Syamsiah Hasyim; Khairul Insan; Usnida Umar; Ulfa Zuhra (Tinta Emas Institute, 2025)
This study aims to analyze the implementation of the Supplementary Feeding Program (PMT) for stunted toddlers in Samataring Village, East Sinjai District, Sinjai Regency, using Edward III’s theory covering four indicators: communication, resources, disposition, and bureaucratic structure. The research employed a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings reveal that the PMT program in Samataring Village has been implemented fairly well. Communication between nutrition officers, posyandu cadres, and the community is carried out directly during posyandu activities and through indirect communication channels. Human resources are adequate, although supporting facilities and infrastructure need improvement. The implementers show a strong commitment to the program, while the bureaucratic structure functions effectively despite the absence of a formal organizational chart. The study implies the need to strengthen facilities and infrastructure, as well as to improve the variety of PMT menus to enhance program effectiveness. Recommendations include increasing local government support, optimizing the role of cadres, and developing innovative nutrition education strategies.